2021
DOI: 10.1002/emp2.12436
|View full text |Cite
|
Sign up to set email alerts
|

What can COVID‐19 teach us about patient satisfaction in the emergency department? A mixed‐methods approach

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
(23 reference statements)
1
10
1
Order By: Relevance
“…The differences were established to be a result of telemedicine [25], which is not the case in the present study. Another study, however, reported significantly less dissatisfied comments about wait time in ED [26]. The shortest length of the wait was 0 min which correlated with the red triage category, meaning the highest priority and immediate admission and treatment.…”
Section: Discussionmentioning
confidence: 87%
“…The differences were established to be a result of telemedicine [25], which is not the case in the present study. Another study, however, reported significantly less dissatisfied comments about wait time in ED [26]. The shortest length of the wait was 0 min which correlated with the red triage category, meaning the highest priority and immediate admission and treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Although not necessarily reflecting the actual quality or standard of clinical services, patient satisfaction is a popular tool to measure quality of health care services 14 , 15 . A patient survey in the emergency department in New York revealed generally higher level of satisfaction among their attendees during the COVID pandemic compared to the preceding years 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring the relationship between COVID-19 and patient satisfaction in the emergency department have tended to compare the overall patient satisfaction levels before and during the pandemic (15,16). In contrast, the present study compares the satisfaction levels of patients treated in the COVID-19 designated area and those treated in the clean area in the emergency department during the pandemic, and is, to the best of our knowledge, the first study to take this approach.…”
Section: Discussionmentioning
confidence: 99%